2009
DOI: 10.1182/blood.v114.22.1048.1048
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Cytarabine (HiDAC) and Mitoxantrone (MITO) Is An Effective Induction Therapy for High-Risk Acute Myeloid Leukemia (AML).

Abstract: 1048 Poster Board I-70 Background: Patients with high risk AML, including those with advanced age, relapsed or refractory disease, unfavorable cytogenetics, therapy-related myeloid neoplasm (t-MN), and multiple medical co-morbidities, carry a poor prognosis and outcomes after 7+3 induction chemotherapy are poor. Complete remission (CR) rates tend to be low and range from 12-63% and induction death rates range from 10-26%. We developed a novel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…High-dose cytarabine (HiDAC) is commonly used for induction of relapsed or refractory AML. At the 2009 ASH meeting, Sarah et al reported a novel, timed-sequential regimen that takes advantage of synergy when mitoxantrone is given after cytarabine [ 14 ]. It was a retrospective analysis of patients with relapsed or refractory high-risk AML.…”
Section: New Regimens For Refractory/relapsed Amlmentioning
confidence: 99%
“…High-dose cytarabine (HiDAC) is commonly used for induction of relapsed or refractory AML. At the 2009 ASH meeting, Sarah et al reported a novel, timed-sequential regimen that takes advantage of synergy when mitoxantrone is given after cytarabine [ 14 ]. It was a retrospective analysis of patients with relapsed or refractory high-risk AML.…”
Section: New Regimens For Refractory/relapsed Amlmentioning
confidence: 99%